2023
DOI: 10.6007/ijarbss/v13-i2/16250
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Students’ Academic Performance in Higher Learning Institutions in Malaysia

Abstract: In this era, competition is everywhere, especially for graduated students who are looking for a job. Graduated students need to equip themselves with the knowledge and soft skills required by the industry. In the industry's view, they recruit and select workers based on selective criteria such as academic qualifications, intelligent, communication skills and ability to work as a team. Therefore, the graduated students are supposedly preparing themselves accordingly. This study aims to identify the factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…To address this issue, it is essential to establish robust mechanisms that monitor and regulate educational standards within these institutions. 94 One recommendation for strengthening oversight is to enhance the capacity of regulatory bodies responsible for monitoring educational standards. These bodies should be adequately funded and empowered to conduct regular inspections and assessments.…”
Section: Strengthening Oversight To Ensure Educational Standardsmentioning
confidence: 99%
“…To address this issue, it is essential to establish robust mechanisms that monitor and regulate educational standards within these institutions. 94 One recommendation for strengthening oversight is to enhance the capacity of regulatory bodies responsible for monitoring educational standards. These bodies should be adequately funded and empowered to conduct regular inspections and assessments.…”
Section: Strengthening Oversight To Ensure Educational Standardsmentioning
confidence: 99%
“…Although much literature studies factors related to academic performance, it mainly focuses on external factors such as financial issues or problems (Norazlan et al, 2020), the influence of friends and family, and school or institutional factors (Zhou & Mustappha, 2022). Besides, students' learning ability and efforts in studying (Bakar et al, 2023) and time management (Mulugeta & Pandian, 2022) have also been found to contribute to the success of academic performance. However, students' soft-skills-related determinants and academic performance need further investigation (Casali et al, 2023;Obilor, 2019) because technical skills are insufficient to succeed in academic performance and industry (Patacsil & Tablatin, 2017).…”
Section: Introductionmentioning
confidence: 99%